The Impact of Exports and Industrial Expansion on the Economic Growth of ASEAN Countries - WATTANAKUL, Thanet (Journal of Advanced Research in Law and Economics, 2017)
This paper investigates the impact of exports and industrial expansion on the economic growth of ASEAN countries, which comprise Brunei, Cambodia, Indonesia, Laos, Malaysia, the Philippines, Singapore, Thailand and Vietnam. This study employs exports and a growth model using annual panel data sets from 1976-2014 which are estimated by the panel dynamic ordinary least squares (DOLS) procedure. The study concludes that the exports and industrial expansion of ASEAN countries have a positive relationship with economic growth. This study can infer that the exports and industrial expansion of ASEAN is of major importance for ASEAN’s economic growth. Therefore, the ASEAN countries should continue focusing on exports and industrial promotion policies by relaxing the barriers to entry for investment as well as implementing potential industrial trade zoning to enhance the regional economic level.